Teaching languages to young learners - Cameron, Lynne (Cambridge language teaching library, 2001)
Recent years have seen rapid growth in the numbers of children being taught foreign languages at younger ages. While course books aimed at young learners are appearing on the market, there is scant theoretical reference in the teacher education literature. Teaching Languages to Young Learners is one of the few to develop readers' understanding of what happens in classrooms where children are being taught a foreign language. It will offer teachers and trainers a coherent theoretical framework to structure thinking about children's language learning. It gives practical advice on how to analyse and evaluate classroom activities, language use and language development. Examples from classrooms in Europe and Asia will help bring alive the realities of working with young learners of English